Предмет:
МатематикаАвтор:
аноним{12 – 2 * (x - 3y) = x + y + 2;
{1,2x + 0,7y + 1,4 = 0.
{12 – 2x + 6y = x + y + 2;
{1,2x + 0,7y + 1,4 = 0.
{10 – 3x + 5y = 0;
{1,2x + 0,7y + 1,4 = 0.
{10 – 3x + 5y = 0 | : 5;
{1,2x + 0,7y + 1,4 = 0.
{2 – 3/5 * x + y = 0;
{1,2x + 0,7y + 1,4 = 0.
{y = 3/5 * x – 2;
{1,2x + 0,7y + 1,4 = 0.
1,2х + 0,7 * (3/5 * х – 2) + 1,4 = 0;
1,2х + 7/10 * 3/5 * х – 14/10 + 14/10 = 0;
12/10 * х + 21/50 * х = 0;
60/50 * х + 21/50 * х = 0;
81/50 * х = 0;
х = 0.
у = 3/5 * 0 – 2;
у = -2.
Проверка:
12 – 2 * 0 + 6 * (-2) = 0 – 2 + 2;
12 – 12 = -2 + 2;
0 = 0.
Ответ: х = 0; у = -2.
Автор:
elena97Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть